Soil-inhabiting mites of the family Laelapidae (Acari: Mesostigmata) from Assiut Governorate, Egypt - Joharchi, Omid; Negm, Mohamed W. (Zootaxa, 2020)
This paper reports on ten species, in six enera, of soil-inhabiting mites of the family Laelapidae from Assiut Governorate, Egypt. The species Androlaelaps projecta Furman, 1972, Gaeolaelaps mirzakhaniae Kazemi & Khalesi, 2018, G. nolli (Karg, 1962), Hypoaspisella asperatus (Berlese, 1904a) comb. nov., Laelaspis calidus Berlese, 1924 and Ololaelaps tasmanicus (Womersely, 1956) are recorded for the first time from Egypt. Supplementary descriptions of some species are presented to facilitate species delimitation. The males of Cosmolaelaps longus (Hafez, Elbadry & Nasr, 1982) and O. tasmanicus are described for the first time.